Decoding Purchase Intention in the Digital Era: The Mediating Role of Brand Passion and Brand Loyalty - Panjaitan, Rahellia (SAFE-Network, 2026)
intention by incorporating brand passion and brand loyalty as mediating constructs, while aligning the analysis with the framework of the Sustainable Development Goals (SDGs). Within the sustainable development perspective, social media communication is expected not only to persuade consumers but also to educate them, consistent with the principles of Education for Sustainable Development (ESD), in order to promote responsible consumption as emphasized in SDG 12. The study uses a quantitative method with an explanatory structure. Data were collected from 132 individuals who are actively using social media, selected through purposive sampling, and then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The main findings reveal that social media communication conveying ethical and sustainability-oriented values significantly enhances both brand passion and brand loyalty. The results of the hypothesis test confirm that the two mediation variables play a crucial role in bridging digital communication with consumer purchase intentions. The emerging trend shows a shift towards ethical consumerism, where consumers are more driven by content that prioritizes the authenticity of social impact rather than aesthetics alone. The implications of this study confirm that the integration of sustainability narratives in social media communication strategies not only supports economic growth (SDG 8), but also creates resilient emotional attachments. Marketing practitioners are advised to adopt an ESD approach in digital content to build long-term loyalty and support the transition to a greener and more responsible market.